Innovative Product and Service Development Based on Customer Needs - Guvo Deswarth Purba; Muhammad Rahman Rizqi (AT-TAFAHUM: Journal of Law, 2022)
The development of innovative products and services is an important strategy in facing increasingly fierce market competition. This study aims to analyze the concept of product development, the process of identifying customer needs, and effective product design in creating added value for consumers. The method used is a literature study with a qualitative descriptive approach based on book sources and scientific references related to entrepreneurship. The results show that the success of product development is greatly influenced by the company's ability to understand customer needs through a systematic identification process, such as customer data analysis and the 5W approach. In addition, structured product design, from planning to design details, is a crucial factor in producing competitive products. Product innovation also plays a key role in creating sustainable competitive advantage. Thus, the integration of innovation, customer needs, and appropriate product design can increase customer satisfaction and support business sustainability in the modern era.